Defective h-MAB phase titanium indium boron negative electrode material and preparation method thereof and application in lithium ion battery
The defects were introduced through mechanical ball milling method to reduce the grain size of Ti2InB2 material, which solved the problem of insufficient performance of the negative electrode material of existing lithium-ion batteries, achieved high discharge specific capacity and excellent cycle and rate performance, and was simple and low-cost.
Patent Information
- Application Number
- CN202311038795.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-17
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-08-17
AI Technical Summary
The low theoretical capacity and poor rate performance of the negative electrode material of the existing lithium-ion battery limit its application in high-power lithium-ion batteries. The existing methods for introducing defects are cumbersome, costly, and poor controllability of the introduced defects.
The defect is created by a simple mechanical ball milling method, which reduces the grain size of Ti2InB2 material, shortens the lithium ion diffusion path, and improves the rate performance and discharge specific capacity of the material.
It achieves high discharge specific capacity and excellent cycle and rate performance. It has simple process, fast, low energy consumption and low cost. It is suitable for widely used in lithium-ion battery negative electrode materials.
Smart Images

Figure CN117208923B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of negative electrode materials for lithium ion batteries, and in particular to a defective h-MAB phase titanium indium boron negative electrode material and a preparation method thereof and application in lithium ion batteries. Background Art
[0002] With the rapid increase in fossil energy consumption and the resulting environmental problems, the development of clean and efficient energy storage technology is of great significance to meet the needs of higher specific energy, higher power density and longer service life. Rechargeable lithium-ion batteries (LIBs) are very attractive portable electronic energy conversion devices that can be used on a large scale. As we all know, graphite material is the first negative electrode material for lithium-ion batteries, but the low theoretical capacity and poor rate performance of graphite limit its application in high-power lithium-ion batteries. The use of high-capacity negative electrode materials is an effective way to improve the performance of LIBs. Therefore, it is urgent to explore and develop new negative electrode materials with high energy density and long life.
[0003] In recent years, transition metal boride MAB phase has attracted more and more researchers' attention due to its layered crystal structure, anisotropic chemical bonding, good heat resistance and oxidation resistance. MAB phase (M is a transition metal atom, A is a IIIA and IVA group element, and B is a boron atom) is a type of ternary layered transition metal boride material similar to MAX phase. Although boron is adjacent to carbon in the periodic table and has certain similarities with carbon, it shows more significant differences, which are specifically reflected in: since boron is a light element with three valence electrons, it is easy to form polyatomic bonds, which helps to overcome electronic defects, thereby producing high reactivity with metal ions and having excellent ionic conductivity. Therefore, MAB phase can obtain higher theoretical capacity as an electrode material and has great potential in improving battery performance.
[0004] In 2019, our team synthesized the first ternary transition metal boride with a hexagonal crystal system - Ti2InB2 for the first time. We found that Ti2InB2 has the same sandwich stacking structure and hexagonal symmetry as the MAX phase, and has the elemental composition of MAB, so it is named hexagonal MAB phase (h-MAB phase). Ti2InB2 is expected to be used as an electrode material due to its layered structure and the high theoretical capacity and good conductivity of the "In" atoms in the middle position. However, the original micron-sized (or larger) h-MAB phase particles cannot make good use of their layered structure and the energy storage function of the "A" position atoms, so they cannot obtain excellent electrochemical performance, which limits their application in electrode materials.
[0005] In recent years, researchers have introduced defects into existing electrode materials through methods such as plasma, microwave, combustion in an inert atmosphere, carbon coating, or substitution of high-valent elements for low-valent elements to increase the specific capacity of the materials. However, on the one hand, the above-mentioned methods of introducing defects are cumbersome and costly; on the other hand, the defects introduced by the above-mentioned methods may change the composition and structure of the material, trigger unnecessary reactions, and cause poor controllability of the material property transformation, causing the material lattice to be distorted, hindering ion diffusion, and thus deteriorating the electrochemical performance of the material. Therefore, it is very meaningful to overcome the problems of defect introduction in the prior art and provide a defective h-MAB phase titanium indium boron negative electrode material for lithium-ion batteries to solve the low theoretical capacity and poor rate performance of graphite materials. Summary of the invention
[0006] In view of the deficiencies in the above-mentioned prior art, the present invention provides a defective h-MAB phase titanium indium boron negative electrode material, a preparation method thereof, and an application in a lithium ion battery. The present invention adopts a simple ball milling operation to produce defects on the Ti2InB2 material, while overcoming the deficiencies in the prior art method of introducing defects and the technical defect of poor electrochemical performance of the Ti2InB2 material. The results show that the obtained defective h-MAB phase titanium indium boron negative electrode material has a hexagonal crystal system and a layered microstructure, the layers are connected by chemical bonds, and have a graphene-like boron layer. The special crystal structure makes the h-MAB phase have novel physical properties, such as being easier to produce defects and vacancies, etc., thereby improving the theoretical capacity and being suitable for use as an electrode material.
[0007] The second purpose of the present invention is to increase the conductivity of the material by creating defects through a simple mechanical ball milling method. The method is simple, fast, low in energy consumption, low in cost, and environmentally friendly.
[0008] The third object of the present invention is to provide a defective h-MAB phase titanium indium boron negative electrode material. The obtained negative electrode material has high discharge specific capacity, good cycle and rate performance, can be widely used in lithium ion battery negative electrode materials, and has good application prospects.
[0009] To achieve the above object, the technical solution of the present invention is as follows:
[0010] A method for preparing a defective h-MAB phase titanium indium boron negative electrode material comprises the following steps:
[0011] (1) Preparation of Ti2InB2 material;
[0012] (2) ball milling the Ti2InB2 material of step (1) to obtain a ball milling product;
[0013] (3) placing the ball-milled product of step (2) in a hydrochloric acid solution and stirring at room temperature for 10-30 hours to obtain a defective h-MAB phase titanium indium boron material, and washing with hydrochloric acid to remove some impurity phases, such as TiB2, Ti3In4, and metal In.
[0014] Preferably, the Ti2InB2 material in step (1) is prepared according to the following steps:
[0015] S1, mixing titanium powder, indium powder and boron powder to obtain a mixed precursor;
[0016] Wherein, the molar ratio of titanium powder, indium powder and boron powder is 1.5-2.5:1-1.5:1.5-28;
[0017] S2. Wrap the mixed precursor of step S1 in molybdenum foil, then load it into a quartz crucible, and then perform high-temperature annealing and calcination under an inert atmosphere to obtain Ti2InB2 material.
[0018] Preferably, the conditions for high temperature annealing and calcination in step S2 are: keeping warm at 1000-1800° C. for 12-48 hours.
[0019] Preferably, the ball milling method in step (2) is: using a ball milling jar and ball milling at a rotation speed of 100-1000 rpm for 1-12 hours.
[0020] Preferably, the ball milling method in step (2) is: using a ball milling jar and ball milling at a rotation speed of 100-1000 rpm for 3-5 hours.
[0021] Preferably, the concentration of the hydrochloric acid solution in step (3) is 1-5 mol / L.
[0022] The present invention also protects the defective h-MAB phase titanium indium boron negative electrode material obtained by the above preparation method. The defective h-MAB phase titanium indium boron negative electrode material has a hexagonal crystal system and a layered microstructure, the layers are connected by chemical bonds, and have a graphene-like boron layer.
[0023] The present invention also protects the use of defective h-MAB phase titanium indium boron negative electrode material in the preparation of negative electrode plates for lithium ion batteries.
[0024] The present invention also protects a lithium-ion battery negative electrode sheet prepared from a defective h-MAB phase titanium indium boron negative electrode material, wherein the lithium-ion battery negative electrode sheet is prepared according to the following steps:
[0025] The defective h-MAB phase titanium indium boron negative electrode material, a conductive agent and a binder are mixed, and then mixed with a solvent to obtain a slurry, and the slurry is evenly coated on the surface of a copper foil as a substrate, and then dried to obtain a lithium ion battery negative electrode sheet;
[0026] Among them, the mass ratio of defective h-MAB phase titanium indium boron negative electrode material, conductive agent and binder is 7-8:1-2:1;
[0027] The conductive agent is selected from conductive carbon black, carbon nanotubes or graphene; the binder is selected from polyvinylidene fluoride or carboxymethyl cellulose; and the solvent is selected from N-methylpyrrolidone.
[0028] The present invention also protects the use of a negative electrode sheet of a lithium ion battery in preparing a lithium ion battery, wherein the lithium ion battery is prepared according to the following steps:
[0029] Positive electrode sheet preparation: pressing and cutting the metallic lithium;
[0030] Preparation of electrolyte: Dissolve LiPF6 in an organic solvent to prepare a LiPF6 electrolyte with a concentration of 0.8 mol / L;
[0031] Wherein, the organic solvent is composed of ethylene carbonate, diethyl carbonate and fluoroethylene carbonate in a volume ratio of 47.5:47.5:5;
[0032] Preparation of lithium-ion battery: The positive electrode plate, Cellgard2400 separator, electrolyte and lithium-ion battery negative electrode plate are assembled in sequence to prepare a lithium-ion battery.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] 1. The present invention adopts a simple mechanical ball milling treatment method to reduce the grain size of Ti2InB2, shorten the diffusion path of lithium ions therein, and thereby improve the rate performance of the material; at the same time, the reduction in grain size can increase the specific surface area of the material, and the appropriate defect concentration provides more active sites for lithium ion deintercalation, thereby improving the discharge specific capacity of the material.
[0035] 2. The preparation of the negative electrode material of the present invention has no requirements on the precursor preparation method, has strong universality, adopts a simple mechanical ball milling method to introduce defects, has a simple process, fast and low energy consumption, a small number of raw materials, low cost, and is environmentally friendly; the negative electrode material Ti2InB2-3 obtained by the present invention has a high discharge specific capacity, good cycle and rate performance, and the prepared product has a high specific capacity of 100mAg -1 The discharge capacity after 200 cycles at the same current density is as high as 350 mAh g -1 , can be widely used in lithium-ion batteries and has good application prospects.
[0036] 3. The present invention introduces defects by reducing the size of Ti2InB2 using a simple mechanical ball milling method without changing the material composition, and the introduction of defects can improve the electronic conductivity of the material. Therefore, when it is used as a negative electrode material for lithium-ion batteries, a higher discharge specific capacity and excellent cycle performance can be obtained.
[0037] 4. The study found that the "A" atoms in the h-MAB phase are relatively active and prone to vacancies and defects. Therefore, the ball milling method is used in this application. During the ball milling process, the Ti2InB2 sheets are broken and reorganized under the action of mechanical force, and the size gradually decreases, forming an irregular broken edge structure; and the middle "In" atoms are broken and detached by mechanical force, forming defects. Thanks to the dual effects of the nanoscale size structure and rich cation defects, the defective Ti2InB2 h-MAB phase exhibits excellent cycle stability and rate performance, showing the good application prospects of h-MAB in the field of energy storage. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 It is an XRD diagram of the defective h-MAB phase titanium indium boron negative electrode material of Examples 1, 2, and 3 of the present invention and the h-MAB phase titanium indium boron negative electrode material of Comparative Example 1;
[0039] Figure 2 This is a SEM image of the h-MAB phase titanium indium boron negative electrode material of Comparative Example 1 of the present invention;
[0040] Figure 3 The h-MAB phase titanium indium boron negative electrode material of comparative example 1 of the present invention is 100mA g -1 Cycling performance diagram under current density;
[0041] Figure 4 is a SEM image of the defective h-MAB phase titanium indium boron negative electrode material of Example 1 of the present invention;
[0042] Figure 5 The defective h-MAB phase titanium indium boron negative electrode material of Example 1 of the present invention is 100mA g -1 Cycling performance diagram under current density;
[0043] Figure 6 is a SEM image of the defective h-MAB phase titanium indium boron negative electrode material of Example 2 of the present invention;
[0044] Figure 7 This is an EPR image of the defective h-MAB phase titanium indium boron negative electrode material of Example 2 of the present invention;
[0045] Figure 8 The defective h-MAB phase titanium indium boron negative electrode material of Example 2 of the present invention is 100mA g -1 Cycling performance diagram under current density;
[0046] Fig. 9 is a SEM image of the defective h-MAB phase titanium indium boron negative electrode material of Example 3 of the present invention;
[0047] Fig.10 The defective h-MAB phase titanium indium boron negative electrode material of Example 3 of the present invention is 100mA g -1 Cycling performance diagram at different current densities. DETAILED DESCRIPTION
[0048] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention. The experimental methods described in the embodiments of the present invention are conventional methods unless otherwise specified.
[0049] Example 1
[0050] A method for preparing a defective h-MAB phase titanium indium boron negative electrode material comprises the following steps:
[0051] (1) Preparation of Ti2InB2 material;
[0052] S1. Weigh titanium powder (purity 99%, 200 mesh), indium powder (purity 99%, 200 mesh) and boron powder (purity 99%, 325 mesh), and shake and mix the above materials for 15 minutes in a molar ratio of 2:1.2:2 to obtain a mixed precursor;
[0053] S2, wrap the mixed precursor in molybdenum foil, then put it into a quartz crucible, and then put it into a high-temperature tube furnace for reaction. The reaction conditions are: reaction temperature 1100°C, insulation time 12h, inert gas protection, after the tube furnace is cooled to room temperature, take out the reaction product in the quartz crucible to obtain Ti2InB2 material;
[0054] (2) The Ti2InB2 material of step (1) is placed in a ball mill, and ball milled at a ball milling speed of 300 rpm for 1 h, and the material is separated from the ball milling medium by a sieve to obtain a ball milling product;
[0055] (3) The ball-milled product of step (2) was placed in 100 mL of hydrochloric acid with a concentration of 2 mol / L and stirred at room temperature for 10 h to obtain a defective h-MAB phase titanium indium boron negative electrode material, which was recorded as Ti2InB2-1.
[0056] Example 2
[0057] A method for preparing a defective h-MAB phase titanium indium boron negative electrode material comprises the following steps:
[0058] (1) Preparation of Ti2InB2 material;
[0059] S1. Weigh titanium powder (purity 99%, 200 mesh), indium powder (purity 99%, 200 mesh) and boron powder (purity 99%, 325 mesh), and shake and mix the above materials for 15 minutes in a molar ratio of 2:1.2:2 to obtain a mixed precursor;
[0060] S2, wrap the mixed precursor in molybdenum foil, then put it into a quartz crucible, and then put it into a high-temperature tube furnace for reaction. The reaction conditions are: reaction temperature 1100°C, insulation time 12h, inert gas protection, after the tube furnace is cooled to room temperature, take out the reaction product in the quartz crucible to obtain Ti2InB2 material;
[0061] (2) The Ti2InB2 material of step (1) is placed in a ball mill, and ball milled at a ball milling speed of 300 rpm for 3 h, and the material is separated from the ball milling medium by a sieve to obtain a ball milling product;
[0062] (3) The ball-milled product of step (2) was placed in 100 mL of hydrochloric acid with a concentration of 2 mol / L and stirred at room temperature for 10 h to obtain a defective h-MAB phase titanium indium boron negative electrode material, which was recorded as Ti2InB2-3.
[0063] Example 3
[0064] A method for preparing a defective h-MAB phase titanium indium boron negative electrode material comprises the following steps:
[0065] (1) Preparation of Ti2InB2 material;
[0066] S1. Weigh titanium powder (purity 99%, 200 mesh), indium powder (purity 99%, 200 mesh) and boron powder (purity 99%, 325 mesh), and shake and mix the above materials for 15 minutes in a molar ratio of 2:1.2:2 to obtain a mixed precursor;
[0067] S2, wrap the mixed precursor in molybdenum foil, then put it into a quartz crucible, and then put it into a high-temperature tube furnace for reaction. The reaction conditions are: reaction temperature 1100°C, insulation time 12h, inert gas protection, after the tube furnace is cooled to room temperature, take out the reaction product in the quartz crucible to obtain Ti2InB2 material;
[0068] (2) The Ti2InB2 material of step (1) is placed in a ball mill, and ball milled at a ball milling speed of 300 rpm for 10 h, and the material is separated from the ball milling medium by a sieve to obtain a ball milling product;
[0069] (3) The obtained ball-milled product was placed in 100 mL of hydrochloric acid with a concentration of 2 mol / L and stirred at room temperature for 10 h to obtain a defective h-MAB phase titanium indium boron negative electrode material, which was recorded as Ti2InB2-10.
[0070] The only difference between Example 2 and Example 1 is that the ball milling time in step (3) is replaced from 1 h to 3 h; the only difference between Example 3 and Example 1 is that the ball milling time in step (3) is replaced from 1 h to 10 h.
[0071] Example 4
[0072] A method for preparing a defective h-MAB phase titanium indium boron negative electrode material comprises the following steps:
[0073] (1) Preparation of Ti2InB2 material;
[0074] S1. Weigh titanium powder (purity 99%, 200 mesh), indium powder (purity 99%, 200 mesh) and boron powder (purity 99%, 325 mesh) at a molar ratio of 1.5:1:1.5, and oscillate and mix the above materials for 10 minutes to obtain a mixed precursor;
[0075] S2, wrap the mixed precursor in molybdenum foil, then put it into a quartz crucible, and then put it into a high-temperature tube furnace for reaction. The reaction conditions are: reaction temperature 1000 ° C, insulation time 48h, inert gas protection, after the tube furnace is cooled to room temperature, take out the reaction product in the quartz crucible to obtain Ti2InB2 material;
[0076] (2) The Ti2InB2 material of step (1) is placed in a ball mill, and ball milled at a ball milling speed of 500 rpm for 12 h, and the material is separated from the ball milling medium by a sieve to obtain a ball milling product;
[0077] (3) The obtained ball-milled product was placed in 100 mL of hydrochloric acid with a concentration of 1 mol / L and stirred at room temperature for 10 h to obtain a defective h-MAB phase titanium indium boron negative electrode material.
[0078] Example 5
[0079] A method for preparing a defective h-MAB phase titanium indium boron negative electrode material comprises the following steps:
[0080] (1) Preparation of Ti2InB2 material;
[0081] S1. Weigh titanium powder (purity 99%, 200 mesh), indium powder (purity 99%, 200 mesh) and boron powder (purity 99%, 325 mesh), and shake and mix the above materials for 20 minutes in a molar ratio of 2.5:1.5:2.8 to obtain a mixed precursor;
[0082] S2, wrap the mixed precursor in molybdenum foil, then put it into a quartz crucible, and then put it into a high-temperature tube furnace for reaction. The reaction conditions are: reaction temperature 1800°C, insulation time 12h, inert gas protection, after the tube furnace is cooled to room temperature, take out the reaction product in the quartz crucible to obtain Ti2InB2 material;
[0083] (2) The Ti2InB2 material of step (1) is placed in a ball mill, and ball milled at a ball milling speed of 1000 rpm for 5 h, and the material is separated from the ball milling medium by a sieve to obtain a ball milling product;
[0084] (3) The obtained ball-milled product was placed in 100 mL of hydrochloric acid with a concentration of 5 mol / L and stirred at room temperature for 10 h to obtain a defective h-MAB phase titanium indium boron negative electrode material.
[0085] Comparative Example 1
[0086] The preparation method of h-MAB phase titanium indium boron negative electrode material comprises the following steps:
[0087] (1) Preparation of Ti2InB2 material;
[0088] S1. Weigh titanium powder (purity 99%, 200 mesh), indium powder (purity 99%, 200 mesh) and boron powder (purity 99%, 325 mesh), and shake and mix the above materials for 15 minutes in a molar ratio of 2:1.2:2 to obtain a mixed precursor;
[0089] S2, wrap the mixed precursor in molybdenum foil, then put it into a quartz crucible, and then put it into a high-temperature tube furnace for reaction. The reaction conditions are: reaction temperature 1100°C, insulation time 12h, inert gas protection, after the tube furnace is cooled to room temperature, take out the reaction product in the quartz crucible to obtain Ti2InB2 material;
[0090] (2) The Ti2InB2 material of step (1) was placed in 100 mL of hydrochloric acid with a concentration of 2 mol / L and stirred at room temperature for 10 h to obtain h-MAB phase titanium indium boron material, which was recorded as Ti2InB2-0.
[0091] Examples 1-5 of the present invention all produce defective h-MAB phase titanium indium boron negative electrode materials with excellent electrochemical performance. The following is a study using the samples of Examples 1-3 and Comparative Example 1 as examples. The specific research methods and results are as follows:
[0092] Research Methodology:
[0093] The defective h-MAB phase titanium indium boron negative electrode material of Examples 1-3 and the h-MAB phase titanium indium boron negative electrode material of Comparative Example 1 are used as active materials of battery negative electrode materials and used in lithium-ion batteries; the negative electrode sheet of the lithium-ion battery is prepared according to the following steps: 80 mg of defective h-MAB phase titanium indium boron negative electrode material, 10 mg of conductive carbon black, and 10 mg of polyvinylidene fluoride are weighed according to a mass ratio of 8:1:1, N-methylpyrrolidone is added dropwise thereto after mixing, and stirred for 20 minutes until a uniform slurry is formed, and then the slurry is evenly coated on the surface of the copper foil with a 100 μm scraper, and after drying in a vacuum drying oven at 60° C. for 12 hours, the copper foil with the active material is cut into disc-shaped negative electrode sheets, and then transferred to a glove box for standby use;
[0094] The assembly of the simulated battery was carried out in a MIKROUNA glove box filled with argon atmosphere, using 0.8 mol / L commercial electrolyte LiPF6 / EC:DEC (1:1) (V:V) as the electrolyte, and a Li metal sheet as the counter electrode, which was assembled together with the negative electrode sheet into a 2032 button cell.
[0095] Research findings:
[0096] Figure 1 3 are XRD diagrams of Examples 1-3 of the present invention and Comparative Example 1. It can be seen from the diagram that the main phase of the material has not changed, indicating that the material has good stability.
[0097] Figure 2 This is the SEM image of Ti2InB2-0 prepared in Example 1. It can be seen from the image that the particles of Ti2InB2-0 are relatively large and are aggregated together.
[0098] Figure 3 This is the cycle performance diagram of the Ti2InB2-0 assembled half-cell prepared in Example 1 at a current density of 100 mA / g. After 200 cycles, the discharge capacity of the material is 180 mAh g -1 .
[0099] Figure 4 This is the SEM image of Ti2InB2-1 prepared in Example 1. From the image, we can see the layered structure of Ti2InB2-1 particles. Figure 2 Relatively scattered.
[0100] Figure 5 This is the cycle performance diagram of the half-cell assembled with Ti2InB2-1 prepared in Example 1 at a current density of 100 mA / g. After 200 cycles, the discharge capacity of the material is as high as 205 mAh g -1 .
[0101] Figure 6This is the SEM image of Ti2InB2-3 prepared in Example 2. It can be seen from the figure that the particle size of Ti2InB2-3 is small. Small particles can shorten the diffusion path of lithium ions and thus improve the material performance.
[0102] Figure 7 This is the EPR graph of Ti2InB2-3 prepared in Example 2. It can be seen from the figure that there are defects in Ti2InB2-3. The presence of an appropriate amount of defects will increase the specific capacity of the material and provide a new pathway for lithium ion diffusion.
[0103] Figure 8 This is the cycle performance diagram of the Ti2InB2-3 assembled half-cell prepared in Example 2 at a current density of 100 mA / g. After 200 cycles, the discharge capacity of the material is as high as 350 mAh g -1 .
[0104] Fig. 9 This is the SEM image of Ti2InB2-10 prepared in Example 3. It can be seen from the image that the particles of Ti2InB2-10 are small in size and agglomerated together.
[0105] Fig.10 This is the cycle performance diagram of the Ti2InB2-10 assembled half-cell prepared in Example 3 at a current density of 100 mA / g. After 200 cycles, the discharge capacity of the material is as high as 293 mAh g -1 .
[0106] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a defective h-MAB phase titanium indium boron negative electrode material, characterized in that: The following steps are involved: (1) Preparation of Ti2InB2 material; (2) ball milling the Ti2InB2 material of step (1) to obtain a ball milling product; (3) placing the ball-milled product of step (2) in a hydrochloric acid solution and stirring at room temperature for 10-30 hours to obtain a defective h-MAB phase titanium indium boron material; The ball milling method in step (2) is: using a ball milling jar and ball milling at a rotation speed of 100-1000 rpm for 1-12 hours.
2. The method for preparing the defective h-MAB phase titanium indium boron negative electrode material according to claim 1, characterized in that: In step (1), the Ti2InB2 material is prepared according to the following steps: S1, mixing titanium powder, indium powder and boron powder to obtain a mixed precursor; Wherein, the molar ratio of titanium powder, indium powder and boron powder is 1.5-2.5:1-1.5:1.5-2.8; S2. Wrap the mixed precursor of step S1 in molybdenum foil, then load it into a quartz crucible, and then perform high-temperature annealing and calcination under an inert atmosphere to obtain Ti2InB2 material.
3. The method for preparing the defective h-MAB phase titanium indium boron negative electrode material according to claim 2, characterized in that: The conditions for high temperature annealing and calcination in step S2 are: keeping the temperature at 1000-1800° C. for 12-48 hours.
4. The method for preparing the defective h-MAB phase titanium indium boron negative electrode material according to claim 1, characterized in that: The ball milling method in step (2) is: using a ball milling jar and ball milling at a rotation speed of 100-1000 rpm for 3-5 hours.
5. The method for preparing the defective h-MAB phase titanium indium boron negative electrode material according to claim 1, characterized in that: The concentration of the hydrochloric acid solution in step (3) is 1-5 mol / L.
6. A defective h-MAB phase titanium indium boron negative electrode material prepared by the preparation method according to any one of claims 1 to 5, characterized in that: The defective h-MAB phase titanium indium boron negative electrode material has a hexagonal crystal system and a layered microstructure, the layers are connected by chemical bonds, and have a graphene-like boron layer.
7. Use of the defective h-MAB phase titanium indium boron negative electrode material according to claim 6 in preparing negative electrode sheets for lithium-ion batteries.
8. A negative electrode sheet for a lithium-ion battery prepared using the defective h-MAB phase titanium indium boron negative electrode material according to claim 6, characterized in that: The negative electrode plate of the lithium ion battery is prepared according to the following steps: The defective h-MAB phase titanium indium boron negative electrode material, a conductive agent and a binder are mixed, and then mixed with a solvent to obtain a slurry, and the slurry is evenly coated on the surface of a copper foil as a substrate, and then dried to obtain a lithium ion battery negative electrode sheet; Among them, the mass ratio of defective h-MAB phase titanium indium boron negative electrode material, conductive agent and binder is 7-8:1-2:1; The conductive agent is selected from conductive carbon black, carbon nanotubes or graphene; the binder is selected from polyvinylidene fluoride or carboxymethyl cellulose; and the solvent is selected from N-methylpyrrolidone.
9. Use of the negative electrode sheet of a lithium ion battery according to claim 8 in preparing a lithium ion battery, characterized in that: The lithium-ion battery is prepared according to the following steps: Positive electrode sheet preparation: pressing and cutting the metallic lithium; Preparation of electrolyte: Dissolve LiPF6 in an organic solvent to prepare a LiPF6 electrolyte with a concentration of 0.8 mol / L; Wherein, the organic solvent is composed of ethylene carbonate, diethyl carbonate and fluoroethylene carbonate in a volume ratio of 47.5:47.5:5; Preparation of lithium-ion battery: The positive electrode plate, Cellgard2400 separator, electrolyte and lithium-ion battery negative electrode plate are assembled in sequence to prepare a lithium-ion battery.
Citation Information
Patent Citations
Amorphous carbon negative electrode material and preparation method and application thereof
CN115881895A